1994
DOI: 10.1083/jcb.126.1.175
|View full text |Cite
|
Sign up to set email alerts
|

The Chlamydomonas FLA10 gene encodes a novel kinesin-homologous protein.

Abstract: Abstract. Many genes on the uni linkage group of Chlamydomonas affect the basal body/flagellar apparatus. Among these are five FLA genes, whose mutations cause temperature-sensitive defects in flagellar assembly. We present the molecular analysis of a gene which maps to fla/0 and functionally rescues the flalO phenotype. Nucleotide sequencing revealed that the gene encodes a kinesin-homologous protein, KHP1. The 87-kD predicted KHP1 protein, like kinesin heavy chain, has an amino-terminal motor domain, a centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
221
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(230 citation statements)
references
References 76 publications
(86 reference statements)
8
221
1
Order By: Relevance
“…The novel feature of KRP85/95 is the ability of its two kinesinlike subunits to heterodimerize, possibly through their coiled-coil stalk domains (121). This may be a general principle, since related KLPs have been identified in mouse (66,122,123), Drosophila (124), Chlamydomonas (125), and Caenorhabditis (44,124), suggesting that these KLPs are members of a new kinesin family (4, 84). Therefore, the potential for KLPs to form different types of oligomers is another mechanism that may be used to generate variation in motor output, and it stresses the importance of identifying and characterizing native motor protein complexes (126).…”
Section: Gaps In Our Understandingmentioning
confidence: 99%
“…The novel feature of KRP85/95 is the ability of its two kinesinlike subunits to heterodimerize, possibly through their coiled-coil stalk domains (121). This may be a general principle, since related KLPs have been identified in mouse (66,122,123), Drosophila (124), Chlamydomonas (125), and Caenorhabditis (44,124), suggesting that these KLPs are members of a new kinesin family (4, 84). Therefore, the potential for KLPs to form different types of oligomers is another mechanism that may be used to generate variation in motor output, and it stresses the importance of identifying and characterizing native motor protein complexes (126).…”
Section: Gaps In Our Understandingmentioning
confidence: 99%
“…A search of sequence data bases with the predicted amino acid sequence using BLAST searches has revealed that an about 340-amino acid-long region in the COOH terminus is highly similar to kinesin heavy chain motor domain and contained all conserved motifs present in the motor domain of the heavy chain of known kinesins and kinesin-like proteins. The Arabidopsis calmodulin-binding protein showed highest sequence similarity with the motor domain of a recently reported kinesin homolog (KHP1) from Chlamy- domonas (58). Because of the similarity of this calmodulinbinding protein with kinesins, we have designated this protein as KCBP.…”
Section: Isolation Of a Kinesin Heavy Chain-like Calmodulin-bindingmentioning
confidence: 99%
“…In the mouse, KIF3A is a subunit of the KIF3 complex, a heterotrimeric kinesin (kinesin-II) composed of three subunits: KIF3A, KIF3B or 3C, and KAP3. The KIF3A subunit of kinesin-II is the mouse ortholog of the Chlamydomonas anterograde IFT motor subunit FLA10 [Walther et al, 1994]. Knockout mice were generated that were kif3A Ϫ/Ϫ ; these mice lack the 3A subunit and thus lack a functional KIF3/kinesin-II complex.…”
Section: Left/right Asymmetrymentioning
confidence: 99%
“…These 17 IFT polypeptides vary in relative molecular mass from 20,000 to 172,000. The IFT rafts are moved in the anterograde direction to the flagellar tip by kinesin-II [Kozminski et al, 1995], a heterotrimeric kinesin; a subunit of kinesin-II is defective in the flagellar mutant fla10 [Walther et al, 1994]. The IFT particles are moved in the retrograde direction to the base of the flagellum by cytoplasmic dynein 1b [Pazour et al, 1998;Porter et al, 1999].…”
Section: Introductionmentioning
confidence: 99%